STRATEGI PENGEMBANGAN OBJEK WISATA AIR TERJUN TUJUH TINGKAT BATANG KOBAN OLEH DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN KUANTAN SINGINGI - Fenti Julia; Geovani Meiwanda (Cross-border, 2022)
The Kuantan Singingi regency area is one of the regencies in Riau Province that has the potential for the development of tourism progress, considering that this area has a strategic position in the border area of 3 provinces, namely Riau, Jambi, and Sumatera Barat. In this study, the strategy for developing a tourist attraction is in an effort to improve the supporting facilities and infrastructure in order to increase the attractiveness and interest of tourists. Besides that, it is also to carry out development and construction of the seven-level batang koban waterfall tourist attraction which has been prepared and planned through programs, and in accordance with the vision and mission of the service that has been stated in the strategic plan of the service. The theoretical concept used is the theory of SWOT analysis according to Siagian (2018:172). The research method used is qualitative with dataa collection techniques through interviews, observation and documentation. Based on the resultsof the SWOT analysis, recommendation for the strategy given is the Aggressive Strategy where this situation is very profitable, because the strengths possessed can be utilized for existing opportunities. The results of this study indicate that the development of a seven-level batang koban waterfall attraction by the tourism and culture office of Kuantan Singingi regency has not run optimalyy, so the resulting strategy can carry out promotions and large events to introduce this tourits attraction and empower the surrounding community in creativity as well as rejuvenating and procuring facilities and infrastructure for supporting needs at the seven-level batang koban waterfall tourist attraction.